Development of Khoa Powder Based Gulabjamun Mix - Yawale, Priya A; Rao, K Jayraj (Indian Journal of Dairy Science, 2012)
Gulabjamun is a popular khoa based sweet in India among all the traditional delicacies. Though it is made from khoa, gulabjamun mix became popular among consumers mainly because of convenience in the preparation procedure. Gulabjamun mix contains skimmed milk powder (SMP), butterfat, maida, suji and baking powder and no khoa component is present. Hence, there is a difference in the quality of gulabjamun made from the ready mix and that made from khoa. The product made from ready mixes lacks typical gulabjamun flavour and texture of the product. In the present study, for improving the flavour and granular texture of the gulabjamun, khoa powder has been used as base material in place of SMP in the gulabjamun mix. The effect of maida and baking powder levels in khoa powder based gulabjamun mix (KP- GMP) on the sensory and textural characteristics of the gulabjamun was studied. Different ratios of khoa powder and maida were tried: 80:20, 70:30 and 60:40. Out of these, use of 30 parts of maida gave best body and texture, flavour and highest overall acceptability of gulabjamun. Further, incorporation of baking powder at 0.5 parts level gave the best quality of gulabjamun with soft and uniform granular texture. The average composition of KP-GMP was: moisture 9.43 per cent, fat 18.94 per cent, protein 14.03 per cent, ash 3.97 per cent and total carbohydrates 53.63 per cent. The shelf life of the KP-GMP was found to be more than 60 days at 300C when packed in LDPE or Metalized pouch.